The Organizational Learning Implementation to Improve Accreditation Performance at the Gayungan Health Center, Surabaya, Indonesia - Reinaldis Sara1 , Ratna Dwi Wulandari2 , Agung Dwi Laksono3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims were to determine the application of organizational learning to improve accreditationperformance. Descriptive research method with a cross-sectional approach. The population in this study wasall employees of Gayungan Health Center with a purposive sampling technique consisting of 13 respondents.Based on the survey results using a questionnaire on the Gayungan Health Center accreditation team; it wasfound that 75% of respondents stated the organizational learning capability and organizational learningprocess were in a good category. The implementation of organizational learning in Gayungan Health Centerwhere employees were directed to continually learn through every activity create innovations in problemsolving and form good teamwork were proven could improve accreditation performance. On the last reaccreditation, Gayungan Health Center got the best accreditation status.